D Endothelium specific insulin resistance leads to accelerated atherosclerosis: a role for reactive oxygen species. (16th May 2012) - Gage, M C; Yuldasheva, N Y; Viswambharan, H; Sukumar, P; Cubbon, R M; Galloway, S; Imrie, H; Skromna, A; Smith, J; Jackson, C; Kearney, M T; Wheatcroft, S B
Abstract : Background: Global insulin resistance and endothelial dysfunction have been identified as predisposing factors for atherosclerosis. However, it is unclear whether selective insulin resistance in endothelial cells alone, is sufficient to promote atherosclerosis. We addressed this question by crossing Endothelial Specific Mutant Insulin Receptor Over-expressing (ESMIRO) mice with ApoE −/− mice. ESMIRO mice over-express a human insulin receptor with an Ala-Thr1134 mutation in the tyrosine kinase domain (which disrupts insulin signalling) selectively in endothelial cells under the control of the tie-2 promoter/enhancer. Methods: Male ApoE −/− /ESMIRO mice were compared with sex-matched littermate ApoE −/− mice (both on a C57Bl6 background) after feeding a Western-style diet for 12 weeks. Results: ApoE −/− /ESMIRO mice were morphologically indistinguishable from ApoE −/− control littermates and showed normal development with no differences between groups in body mass. Heart rate, systolic blood pressure, glucose tolerance, insulin sensitivity and fasting glucose levels were similar in ApoE −/− /ESMIRO and ApoE −/− mice. ApoE −/− /ESMIRO cultured endothelial cells demonstrated insulin resistance through significantly reduced insulin mediated eNOS activity (p=0.003). Aortic lipid deposition along the whole aorta, assessed by en-face oil red O staining, was similar in ApoE −/− ESMIRO and ApoE −/− mice (6.4%±0.5% vs 5.8%±0.5%; p=0.39). Analysis of lipid deposition along the lesser curvature of the aortic arch revealed a significant increase in ApoE −/− ESMIRO when compared to controls (9.4±0.89 vs 12.43±1.19% p=0.035). Atherosclerotic lesion area in cross sections of aortic sinus was also significantly increased in ApoE −/− /ESMIRO mice compared to ApoE −/− controls (24.8%±2.4% vs 16.6%±2.4%; p=0.02). Vascular function assessed through relaxation responses of aortic rings in response to the endothelial specific vasodilator acetylcholine revealed that aortic rings from ApoE −/− /ESMIRO mice had blunted relaxation responses to acetylcholine (Emax ApoE −/− 102.88±6, Emax ApoE −/− /ESMIRO 65±41%, p=0.02), which was restored by the superoxide dismutase mimetic and antioxidant MnTMPyP (Emax ApoE −/− /ESMIRO without MnTMPyP 65±41%, with MnTMPyP 112±15% p=0.048). Endothelial cells from ApoE −/− /ESMIRO mice had significantly increased basal generation of superoxide (1.87-fold increase compared to ApoE −/− p<0.05) which was blunted by the selective NADPH oxidase inhibitor gp91ds-tat (11% reduction ±0.02, p=0.03) and the non-selective NO synthase inhibitor L-NMMA (6% reduction ±0.01, p=0.03). Conclusions: Endothelial specific insulin resistance is sufficient to promote atherosclerosis and increase lesion area in ApoE null mice potentially via the increased ROS displayed in this model. This suggests that enhancing endothelial insulin sensitivity may be an appropriate target to prevent atherosclerosis in insulin-resistant conditions.